EFFECTIVENESS OF UNDERWATER DIP LAMPS (LACUDA) AND CONVENTIONAL LED LAMPS IN CENTRAL BANGKA WATERS: EFEKTIVITAS LAMPU CELUP BAWAH AIR (LACUDA) DAN LAMPU LED KONVENSIONAL DI PERAIRAN BANGKA TENGAH - Imron, Mohammad; Kurnia, Triono Aries; Kusumastuti, Ratih; Wardani, Puti Nursitaning Kusuma; Hendayana, Yomivin Varel (Jurnal Teknologi Perikanan dan Kelautan, 2025)
The development of auxiliary fishing device technology for lift nets has progressed rapidly, particularly in the use of underwater dip lamps (LACUDA) and conventional LED lights. Variations in light type, color, and lamp operating methods influence catch quantity, composition, and productivity. This study aims to compare the fishing performance of fixed lift nets using 750-watt green underwater dip lamps (LACUDA) and 600-watt white conventional LED lights. Field research was conducted in October–November 2024 across six fishing trips with 18 hauls. Data collected consisting of catch productivity and composition were analyzed using descriptive statistics and the Mann–Whitney U-test. Results showed that the productivity of fixed lift nets using underwater dip lamps (LACUDA) reached 10.07, higher than 8.34 from conventional LED lights. The total catch weight of LACUDA was 181.3 kg, compared to 150.1 kg for conventional LEDs. Moreover, catch composition under LACUDA lighting was more diverse, comprising five species—smoothbelly sardinella (Amblygaster leiogaster), Bangka squid (Uroteuthis chinensis), doublespotted queenfish (Scomberoides lysan), yellowstripe scad (Selaroides leptolepis), and anchovy (Stolephorus indicus). In contrast, conventional LED catches included only four species, lacking anchovy. These findings demonstrate that underwater dip lamps (LACUDA) enhance both catch productivity and species diversity compared to conventional LED lights in fixed lift net operations.